When Mycobacterium abscessus strikes: when bacteremia meets vertebral osteomyelitis - Zainulabid, Ummu Afeera; Hussin, Fara Rahidah; Kori, Najma; Ramankutty, Sreeambal; Aziz, Muhammad Nazri; Periyasamy, Petrick; Yuhana, Muhammad Yazli (2023)
Mycobacterium abscessus is a rapidly growing nontuberculous mycobacterium that can cause a wide range of infections in humans, including skin and soft tissue infections, respiratory infections, and bloodstream infections. Although rare, bacteremia and vertebral osteomyelitis are serious and debilitating manifestations of this infection that can result in significant morbidity and mortality.